2013
DOI: 10.1016/j.rser.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth, energy consumption, financial development, international trade and CO2 emissions in Indonesia

Abstract: This study examines the linkages among economic growth, energy consumption, financial development, trade openness and CO 2 emissions over the period of 1975Q 1 -2011Q 4 in the case of Indonesia. The stationary analysis is performed by using Zivot-Andrews structural break unit root test and the ARDL bounds testing approach for a long run relationship between the series in the presence of structural breaks. The causal relation between the concerned variable is examined by the VECM Granger causality technique and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
571
7
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,183 publications
(662 citation statements)
references
References 101 publications
67
571
7
17
Order By: Relevance
“…Similar findings found by Shahbaz et al (2013) where the linkages between economic growths to CO2 emissions in Indonesia over the period of 1975-2011 are unidirectional. Jahangir et al (2012) did a case study to test the causality of CO2 emissions and GDP for Bangladesh.…”
Section: Resultssupporting
confidence: 78%
“…Similar findings found by Shahbaz et al (2013) where the linkages between economic growths to CO2 emissions in Indonesia over the period of 1975-2011 are unidirectional. Jahangir et al (2012) did a case study to test the causality of CO2 emissions and GDP for Bangladesh.…”
Section: Resultssupporting
confidence: 78%
“…They reported that electricity consumption causes CO 2 emissions. For the Indonesian economy, Shahbaz et al (2013c) documented the bidirectional causality between economic growth and CO 2 emissions and between energy consumption and economic growth. In the case of Tunisia, Shahbaz et al (2014b) investigated the causal relationship between energy consumption, economic growth, and CO 2 emissions and noted that CO 2 emissions and energy consumption cause economic growth.…”
Section: Studies On the Nexus Between Energy Consumption Co 2 Emissimentioning
confidence: 99%
“…However, there is negative relationship between stock market activity and energy consumption (Hasnaoui, 2014). Shahbaz, Hye, Tiwari, and Leitão (2013) documented that an increase in CO2 is derived by increased economic growth and energy consumptions. However, financial development and traded openness reduced it.…”
Section: Literature Reviewmentioning
confidence: 99%